2018
DOI: 10.14419/ijet.v7i2.20.11735
|View full text |Cite
|
Sign up to set email alerts
|

Factors of employability skills of engineering graduates: An analytical study using Friedman Test Multiple Regression

Abstract: Employability skills and placement rate becomes the buzz words to bench mark for the quality of engineering education among the technical institutes in the country. The gap between pass out ratio and placement ratio among the engineering graduates is alarming and indicating the poor levels of skill set of the engineers. The reasons for the same are many and multifold. The present paper is focused on studying the role of personal factors, life skills factors, teaching and learning factors, and evaluation system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In contrast, engineers' least commonly associated traits were sensitivity, empathy, fairness, tolerance, and positivity [17]. In India in 2018, it was identified that the gap between the pass-out ratio and placement ratio among the engineering graduates was alarming and indicated the engineers' poor skill set [18]. Further, this study recommends organising structured practical sessions, applicationoriented training, strict evaluation systems, and options for improvement to help the students realise and learn the required skills and improve employability among the engineering graduates in the sample [18].…”
Section: Employability Skillsmentioning
confidence: 99%
“…In contrast, engineers' least commonly associated traits were sensitivity, empathy, fairness, tolerance, and positivity [17]. In India in 2018, it was identified that the gap between the pass-out ratio and placement ratio among the engineering graduates was alarming and indicated the engineers' poor skill set [18]. Further, this study recommends organising structured practical sessions, applicationoriented training, strict evaluation systems, and options for improvement to help the students realise and learn the required skills and improve employability among the engineering graduates in the sample [18].…”
Section: Employability Skillsmentioning
confidence: 99%
“…The reasons for the same are many and multifold. The present paper is focused on studying the role of personal factors, life skills factors, teaching and learning factors, and evaluation systems and improvement practices environment in the employability of the engineering graduates from Hyderabad city (Roja Rani , 2018)…”
mentioning
confidence: 99%